Revisiting the Feldstein-Horioka puzzle for Turkey - Şule Akkoyunlu (Journal of Applied Economics, 2020)
The domestic saving and investment correlation as posited by Feldstein and Horioka is revisited for Turkey and tested over the whole period (1950-2017) and the two subperiods (1950-1989 and 1990-2017). The time-series properties of the data and the presence of structural breaks are properly addressed by the bounds testing procedure. Although, the investment and savings are positively correlated during the period of restricted capital mobility (1950-1989) and negatively correlated during the period of perfect capital mobility (1990-2017) according to the joint F-test on the significance of the coefficients, the long-run elasticity of investment with respect to savings ratio is significant for the whole period and for the first sub-period. The results confirm the Feldstein and Horioka hypothesis in a closed economy. However, the high, negative and insignificant long-run elasticity and non-constant coefficients in the second sub-period necessitate a full-investment model.
Keywords: 330; bounds testing procedure; capital mobility; Feldstein-Horioka puzzle; Turkey